Early intracardiac thrombosis in preterm infants and thrombolysis with recombinant tissue type plasminogen activator. Issue 1 (1st July 2001) - Ferrari, F; Vagnarelli, F; Gargano, G; Roversi, M F; Biagioni, O; Ranzi, A; Cavazzuti, G B
Abstract : OBJECTIVES: To determine the incidence of catheter related thrombosis and to test the efficacy of recombinant tissue type plasminogen activator (rt-PA) in preterm infants. STUDY DESIGN: From January 1995 to December 1998, echocardiography was performed in the first few days of life in 76 very low birthweight (⩽ 1500 g) infants out of a total of 147 having an umbilical catheter placed. When intracardiac thrombosis was diagnosed, rt-PA infusion was performed. RESULTS: Four infants (5%) developed an intracardiac thrombosis during the first few days of life. In three of them, rt-PA at a dose of 0.4–0.5 mg/kg in a 20–30 minute bolus led to dissolution of the clot. One patient received a three hour infusion after the bolus, at a dose of 0.1 mg/kg/h, with resolution of the thrombus. No systemic effects were observed after rt-PA infusion. CONCLUSIONS: Early thrombosis may occur as a complication of umbilical catheterisation in preterm infants; early echocardiographic detection of this disorder allows complete, safe, and rapid lysis with rt-PA.